Funktsional'naya podgotovlennost' yunykh futbolistov 15-16 let v godichnom tsikle - Nistratov, E. D. (Teorija i Praktika fiziceskoj Kul'tury, 2000)
Analysis of the functional preparedness of young football players in the training year. The results are: 1. An increase of load volume up to 20 h a week has a positive influence on the functional preparedness of young football players. 2. The relationship between unspecific to specific loads of 50:50 is more effective than a 30:70 one. 3. For diagnostics and control the following parameters are suitable: VO2max, anaerob threshold, CO2exp.